Risk Assessment of Dust Extremes and Mud Deposition on Human Activity in the Southwest of Iran. - Mohammad Rahimi; Maede Nasry; Saeed Zalzadeh (Desert)
Climate changes have a significant effect on dust extremes. Dust extremes in humid ambient air can simultaneously or successively form wet mud deposition on the surface of urban areas. The mud deposition on the power network systems and devices causes irreversible damage and significantly influences system performance and efficiency in southwest Iran. This often results in blackouts that cause problems in the operation of urban infrastructure and people's daily activities for up to several days. Khuzestan province was chosen as the case study in this study, and the climatic conditions and risk assessment of mud formation in this area were investigated. Data on a diurnal and monthly timescale of dust and humidity level was used for assessing extreme dust and wet conditions. The data was taken from Khuzestan synoptic station 8 over 11 years (2009-2019). The multivariate copula-based framework is used to calculate univariate and bivariate return periods of mud deposition hazard. The results imply that dust anomalies increase the probability of dust extreme coincidence with wet extreme and occurrence of wet mud hazards in the cold seasons of the year. In addition, limited adaptive capacity, shortage of information, and poor coordination and cooperation by the authorities caused the large-scale impact of the wet mud hazard in Khuzestan. Considering only relative humidity data, the return period of 2017 Khuzestan mud adhesion hazard is approximately 12 to 43 years. If we consider only dust, the return period of 2017 Khuzestan mud adhesion hazard is estimated at 80 to 700 years. However, for both dust and relative humidity extremes, the joint return periods for TDR (Dust and Relative humidity) and T'DR (Dust or Relative humidity) are respectively estimated greater than 200 and lower than 20 years.